Вплив екстракту кріоконсервованих фрагментів шкіри поросят і фулерену С60 на альтеративні та репаративні процеси в шкірі після кріодеструкції (експериментальне дослідження) - Власов, Олександр О. (Автореф. дис. ... канд. мед. наук : 14.01.35. Харків, 2021. 20 с., 2021)
Дисертаційна робота присвячена оптимізації лікування ран після кріоабляції шкіри шляхом застосування екстракту кріоконсервованих фрагментів шкіри поросят (ЕКФШП) та, в порівняльному аспекті, водного колоїдного розчину немодифікованого фулерену С60 (ВКРФ С60). Введення ЕКФШП та ВКРФ С60 прискорює загоювання ран після кріодеструкції шкіри, що проявляється зменшенням проявів деструкції і запалення, та стимуляцією репаративних процесів на місцевому і системному рівнях. Застосування ЕКФШП приводить до органотипової регенерації тканин. Введення ВКРФ С60 викликає дисбаланс процесів проліферації і апоптотозу в тканинах після кріодеструкції шкіри.---------------------------------------------------------------------------------------------------------------------------------------------------------------------------The thesis is devoted to the optimization of wound healing after skin cryoablation by applying a combination of regulatory compounds of animal origin, being a part piglets' skin cryopreserved fragments’ extract (PSCFE) and aqueous colloidal solution of unmodified fullerene C60 (AQSUF C60) in a comparative aspect. An experimental model of tissue destruction and repair after skin cryoablation in hairless rats has been presented, which is characterized with local and systemic manifestations of destruction and inflammation as well as can be used to investigate the processes that occur after cryosurgical treatment of tumors. In cryotherapy there was a sharp decrease in temperature at the point of contact of the applicator and skin down to -75.5 ± 7.9 °C with a gradual rise in temperature to -59.1 ± 6.5 °C. It was found that the biological effects of introducing of an aqueous colloidal solution of fullerene C60 at a dose of 1 mg / kg into the abdominal cavity depended on its concentration. A solution with a concentration of 173 μmol / l has less activity than the one with a concentration of 34.7 μmol / l, that was related to its lower bioavailability due to aggregation and precipitation of fullerene as a deposit at the injection site. It was found that the introduction of PSCFE and AQSUF C60 accelerated the wound healing after skin cryoablation, that was indicated by a reduction in the destruction and inflammation manifestations, and stimulation of reparative processes at the local and systemic levels. The introduction of PSCFE and AQSUF C60 stimulated proliferative activity in epidermis, that led to an increase in the thickness of its layer in marginal areas of the wound; contributed to faster cleansing of the wound from necrotized tissues, evidenced by a decrease in the thickness of the area of primary and secondary necrosis; enhanced the thickness of the demarcation leukocyte shaft; accelerated the filling of the wound defect with granulation tissue; reduced the severity of hemodynamic abnormalities and infiltration of cells into the adjacent wound defect of the dermis, hypodermis and muscle tissue. It was demonstrated that the administration of PSCFE and AQSUF C60 to rats after skin cryoablation contributed to a decrease in serum levels of markers of destructive and inflammatory processes, manifested by normalization of diene conjugates, TBA-active products, C-reactive protein and ceruloplasmin, as well as increased activity of superoxide dismutase and catalase. The use of PSCFE (peptide dose of 0.5 mg / kg μg/ml) led to organotypic tissue regeneration after cryodestruction, and can be recommended for further studying the possibility of its application in clinical practice. The introduction of AQSUF C60 (fullerene dose of 0.5 mg / kg) caused an imbalance of proliferation and apoptosis in the tissues after skin cryoablation. Stimulation of cell proliferation and decrease in apoptotic activity in epithelium and fibroblastic cells were observed.
Effect of extract of cryopreserved piglet`s skin fragments and fullerene C60 on alterative and regenerative processes in skin after cryodestruction (experimental study)
Власов О,О. Вплив екстракту кріоконсервованих фрагментів шкіри поросят і фулерену С60 на альтеративні та репаративні процеси в шкірі після кріодеструкції (експериментальне дослідження): автореф. дис. ... канд. мед. наук : 14.01.35. Харків, 2021. 20 с.
Keywords: кріодеструкція шкіри; рани; регенерація; екстракт шкіри; фуллерен; wounds; regeneration; skin extract; fullerene